APOBEC3G rescues cells from the deleterious effects of DNA damage. (11th June 2021) - Botvinnik, Alexander; Shivam, Pushkar; Smith, Yoav; Sharma, Gunjan; Olshevsky, Udy; Moshel, Ofra; Manevitch, Zakhariya; Climent, Nuria; Oliva, Harold; Britan‐Rosich, Elena; Kotler, Moshe
Abstract : Human apolipoprotein B mRNA editing enzyme, catalytic polypeptide‐like 3G (hA3G), a member of the APOBEC family, was described as an anti‐HIV‐1 restriction factor, deaminating reverse transcripts of the HIV‐1 genome. Several types of cancer cells that express high levels of A3G, such as diffuse large B‐cell lymphoma cells and glioblastomas, show enhanced cell survival after ionizing radiation and chemotherapy treatments. Previously, we showed that hA3G promotes (DNA) double‐strand breaks repair in cultured cells and rescues transgenic mice from a lethal dose of ionizing radiation. Here, we show that A3G rescues cells from the detrimental effects of DNA damage induced by ultraviolet irradiation and by combined bromodeoxyuridine and ultraviolet treatments. The combined treatments stimulate the synthesis of cellular proteins, which are exclusively associated with A3G expression. These proteins participate mainly in nucleotide excision repair and homologous recombination DNA repair pathways. Our results implicate A3G inhibition as a potential strategy for increasing tumor cell sensitivity to genotoxic treatments. Abstract : APOBEC3G promotes DNA damage repair following ultraviolet (UV) irradiation. Following induction of DNA lesions by bromodeoxyuridine + UV, APOBEC3G (A3G) expression is associated with up‐regulation of nucleotide excision repair‐related repair proteins. Silencing of A3G reduces the ability of A3G to repair the bromodeoxyuridine + UV‐induced lesions. Proposed model for A3G activity during the repair of UV lesion via nucleotide excision repair includes deoxycytidine > deoxyuridine deamination at close proximity to the UV‐mediated dimers, followed by recruitment of N ‐glycosylase and subsequent excision of the single‐strand DNA fragment bearing the UV lesion.